Decontextualizing a Ban on Begging: A Multimodal Critical Analysis of Media and Political Discourse in Sweden (Critical Romani Studies, 2024)
This article examines the representation of Romani migrants in the context of the 2016 debates to ban begging in Sweden, highlighting the ways in which media and political discourse misrepresented, simplified, or omitted the complexities surrounding this controversial policy. Drawing on Multimodal Critical Discourse Analysis (MCDA) of media reports from two leading Swedish newspapers, this article reveals that media and political discourse often decontextualize the ban by employing three key strategies: (1) generalization and polarization, (2) victimizing the general public, and (3) concealing the historical and global context of marginalization and poverty. By portraying begging as an undignified and harmful practice, media and political discourse deflect attention away from the systemic inequalities and socio-economic conditions that lead to begging. This article argues that this decontextualization serves to legitimize and reinforce the ban on begging, creating a self-perpetuating cycle that obstructs meaningful dialogue and prevents the implementation of more effective and compassionate policy solutions that address the root causes of begging in Sweden.
Keywords: Anti-Roma racism; colourblind racism; Romaphobia; Swedish media; Ban on begging; multimodal critical discourse analysis (MCDA)